2016
DOI: 10.1016/j.anaerobe.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of arsenic resistance genes in the obligate anaerobe Bacteroides vulgatus ATCC 8482, a gut microbiome bacterium

Abstract: The response of the obligate anaerobe Bacteroides vulgatus ATCC 8482, a common human gut microbiota, to arsenic was determined. B. vulgatus ATCC 8482 is highly resistant to pentavalent As(V) and methylarsenate (MAs(V)). It is somewhat more sensitive to trivalent inorganic As(III) but 100-fold more sensitive to methylarsenite (MAs(III)) than to As(III). B. vulgatus ATCC 8482 has eight continuous genes in its genome that we demonstrate form an arsenical-inducible transcriptional unit. The first gene of this ars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Bacterial species that belong to the phylum Deferribacteres are known to harbor arsenic resistance genes (54); thus, in our study it is tempting to speculate that the observed changes in the abundance of bacterial population may represent one of the mechanisms adapted by neonatal animals for surviving the toxic effects of the arsenite. In particular, the arsenic-inducible transcriptional unit (arsD) conferred resistance to trivalent arsenic species, with MMA III being the most effective inducer, followed by As III (21). Ileal tissue showed efficient conversion of arsenite into pentavalent and trivalent methylated metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial species that belong to the phylum Deferribacteres are known to harbor arsenic resistance genes (54); thus, in our study it is tempting to speculate that the observed changes in the abundance of bacterial population may represent one of the mechanisms adapted by neonatal animals for surviving the toxic effects of the arsenite. In particular, the arsenic-inducible transcriptional unit (arsD) conferred resistance to trivalent arsenic species, with MMA III being the most effective inducer, followed by As III (21). Ileal tissue showed efficient conversion of arsenite into pentavalent and trivalent methylated metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial genera, including Bacteroides, Clostridium, Alistipes, and Bilophila, carry As resistance genes, with an ability to methylate As (19,20). Bacteroides vulgatus possesses an arsenic resistance operon consisting of eight continuous genes, with functions as an As(III)-responsive transcriptional repressor (arsR) and in detoxification of inorganic arsenic (arsDABC), whereas the functions of the other three genes (orf1, orf2, and orf3) in arsenic resistance are unknown (21).…”
mentioning
confidence: 99%
“…However, organoarsenicals such as those generated by ArsM in prokaryotes and As3mt in eukaryotes could also act as powerful toxins. This would make resistance systems necessary not only for protection against environmentally occurring organoarsenicals but also against toxins such as MMA(III) or DMA(III) that are much more toxic than inorganic As(III) ( Li et al, 2016a ). Methylated organoarsenicals are only highly toxic in an anaerobic reducing environment so the toxin can only be effective by close cell to cell contact and keeping a reducing environment under aerobic conditions.…”
Section: Resistance To Organoarsenicalsmentioning
confidence: 99%
“…Similarly, the probiotic strains of Lactobacillus rhamnosus, Propionibacterium freudenreichii and Shermanii js. showed an effective ability to bind cadmium and lead, both in vitro and in experimental mouse model of oral heavy metal intoxication [60,61]. Additionally, use of probiotics improved the nutritional, biochemical and physiological parameters in experimental rat model intoxicated with chromium, suggesting that probiotic bacteria neutralize the toxic effects of chromium [62].…”
Section: The Cellular Composition Of the Complex Barrier Of The Smallmentioning
confidence: 99%